Factors Influencing Affective Organizational Commitment Among Knowledge Workers: A Case Study at Jabatan Pengairan dan Saliran (JPS), Kelantan - Mimi Syazwani, Abd Malek (2010)
This study was carried out to identify The Affective Organizational Commitment among Knowledge Workers in Jabatan Pengairan dan Saliran (JPS), Kelantan. The purpose of the present study is to develop understanding of organizational commitment and to examine whether there is relationship between independent variable (leaderships, knowledge sharing, task orientation, opportunities of training and development, compensation and incentives, and employee relations) with the dependent variable (affective organizational commitment). There are 150 questionnaires were distributed to staff at JPS that have recognized and the response obtained was 100 per cent. The data obtained from the study was analyzed using descriptive statistics. Descriptive statistics was conducted to determine response rate and the profiles of the respondents. Pearson correlation analysis was conducted to examine the relationship between independent variable with the affective organizational commitment. Multiple regressions were use shows that leaderships having the most influence on the organizational commitment among five dimensions of independent. The findings from this study were indicated that there was significant relationship between independent variables with organizational commitment. This is confirming that leadership, knowledge sharing, task orientation, opportunities of training and development, compensation and incentives and employee relations is very important to ensure that the organization's goals achieved as a whole. Hence, Human Resource Managers should take pro active to improve better job environment and ensuring the organizational commitment among the knowledge workers.